1995
DOI: 10.1121/1.413469
|View full text |Cite
|
Sign up to set email alerts
|

An articulatory study of fricative consonants using magnetic resonance imaging

Abstract: Magnetic resonance images of the vocal tract during sustained production of the fricatives/s, •, f, 0, z, 3, v, 6/by four subjects are analyzed. Measurements of vocal-tract lengths and area functions, and morphological analyses of the vocal tract and tongue shapes for these sounds are presented. Interspeaker differences in area functions are found to be greater in the pharyngeal cavity than in the buccal cavity with the nonstriden: fricatives exhibiting greater differences than the strident ones. The anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 1 publication
8
128
0
4
Order By: Relevance
“…Excluding the male subject for the consonant /f/, all pharynx volumes measured were superior to the oral cavity volumes. The study in [14] also found larger pharyngeal volumes in voiced fricatives by means of vocal tract lengths and area function measurements. Equivalent results were also reported in [16] where the authors observed some supraglottal volume changes of pharyngeal articulation during the production of voiced and voiceless fricative consonants.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Excluding the male subject for the consonant /f/, all pharynx volumes measured were superior to the oral cavity volumes. The study in [14] also found larger pharyngeal volumes in voiced fricatives by means of vocal tract lengths and area function measurements. Equivalent results were also reported in [16] where the authors observed some supraglottal volume changes of pharyngeal articulation during the production of voiced and voiceless fricative consonants.…”
Section: Discussionmentioning
confidence: 86%
“…The task of modelling the vocal tract for articulatory synthesis systems aims to obtain the complete geometrical information concerning the vocal tract measured by different techniques, especially MRI [11,14]. Currently, the use of MRI in speech research provides useful and accurate qualitative and quantitative data of speech articulation [21,22,23,24].…”
Section: Measuring and Modelling Speech: A Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to establish the relationship between vocal tract shape and speech sounds, the lateral view of the vocal tract is insufficient, and the 3D vocal tract configuration must be obtained. Since magnetic resonance imaging (MRI) is capable of the 3D measurement of the body in multi-slice images, this technique has been applied to direct measurement of the vocal tract shape and area function [38][39][40][41][42]. Although the MRI provides a powerful visualization technique for speech research, it has a few problems; low signals from the teeth make toothless images, supine position of the subjects can affect natural articulation, and intense machine noise inhibits highquality audio recording.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…MRI imaging has been used to reconstruct 3-D airway volumes for static sounds-vowels and fricatives [7,8,9]-but not to extract tongue features. The current MRI dataset consists of four midsagittal test images of the tongue: at rest, and saying /a /, /i/ and /u/.…”
Section: Image Processingmentioning
confidence: 99%